Motivating factors and barriers towards exercise in severe mental illness: a systematic review and meta-analysis. Issue 14 (9th August 2016) - Firth, J.; Rosenbaum, S.; Stubbs, B.; Gorczynski, P.; Yung, A. R.; Vancampfort, D.
Abstract : Exercise can improve clinical outcomes in people with severe mental illness (SMI). However, this population typically engages in low levels of physical activity with poor adherence to exercise interventions. Understanding the motivating factors and barriers towards exercise for people with SMI would help to maximize exercise participation. A search of major electronic databases was conducted from inception until May 2016. Quantitative studies providing proportional data on the motivating factors and/or barriers towards exercise among patients with SMI were eligible. Random-effects meta-analyses were undertaken to calculate proportional data and 95% confidence intervals (CI) for motivating factors and barriers toward exercise. From 1468 studies, 12 independent studies of 6431 psychiatric patients were eligible for inclusion. Meta-analyses showed that 91% of people with SMI endorsed 'improving health' as a reason for exercise ( N = 6, n = 790, 95% CI 80–94). Among specific aspects of health and well-being, the most common motivations were 'losing weight' (83% of patients), 'improving mood' (81%) and 'reducing stress' (78%). However, low mood and stress were also identified as the most prevalent barriers towards exercise (61% of patients), followed by 'lack of support' (50%). Many of the desirable outcomes of exercise for people with SMI, such as mood improvement, stress reduction and increased energy, are inversely related to the barriers of depression, stress and fatigue which frequently restrict their participation in exercise. Providing patients with professional support to identify and achieve their exercise goals may enable them to overcome psychological barriers, and maintain motivation towards regular physical activity.